2019
DOI: 10.1155/2019/2587245
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Effect of Autologous Platelet Concentrates to Coronally Advanced Flap in the Treatment of Gingival Recessions: A Systematic Review and Meta-Analysis

Abstract: Background. To improve the efficacy of regenerative treatment for gingival recessions, the autologous platelet concentrates (APCs) combined with coronally advanced flap (CAF) have been investigated. However, few studies systematically assess the complementary effect of APCs in periodontal regeneration. The present study aims to evaluate the additional effect of different types of APCs to CAF in the treatment of gingival recessions. Methods. Electronic databases (EMBASE, MEDLINE, and Cochrane Central Register o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…In Dentistry, more specifically in periodontal surgery, questions have emerged about the use of PRF membranes with favorable results. Studies have suggested it as a possible substitute for a connective tissue graft, which is still considered the “gold standard” for soft tissue surgery [ 16 , 30 ]. In oral surgery, favorable results have been found for the insertion of membranes inside of fresh socket after extraction or using it in the treatment for bone lesions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Dentistry, more specifically in periodontal surgery, questions have emerged about the use of PRF membranes with favorable results. Studies have suggested it as a possible substitute for a connective tissue graft, which is still considered the “gold standard” for soft tissue surgery [ 16 , 30 ]. In oral surgery, favorable results have been found for the insertion of membranes inside of fresh socket after extraction or using it in the treatment for bone lesions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In oral surgery, favorable results have been found for the insertion of membranes inside of fresh socket after extraction or using it in the treatment for bone lesions [ 31 ]. Furthermore, the use of a PRF membrane avoids a donor site which greatly decreases the postoperative discomfort [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup analysis was carried out to address the possible differences among the outcomes of the studies regarding the selection of recession type (single or multiple adjacent recessions). This aspect has not been considered in the previous systematic reviews [ 28 , 29 ]. The results of heterogeneity among the subgroups were varied and were found to be greater than 91.3% for GT and 32.8% for WKG.…”
Section: Discussionmentioning
confidence: 99%
“…Since the comparison of CAF + L-PRF versus CAF + CTG was not significant, L-PRF was suggested as a substitute to CTG which has the potential to show a beneficial outcome on bone and keratinized tissue healing, as well as postoperative discomfort reduction. Recently, Li et al [ 29 ] evaluated the effect of autologous platelet concentrates when used with CAF. They included 5 studies to assess the effect of L-PRF and showed L-PRF could exert an additive effect to CAF.…”
Section: Introductionmentioning
confidence: 99%
“… 28 A recent meta-analysis showed that CGF, but not PRP, influenced therapeutic outcomes in the management of gingival recession. 29 However, research into the effect of CGF on photoaging is lacking. The current study was conducted to investigate the therapeutic effect of CGF on photoaging in a nude mouse model.…”
Section: Introductionmentioning
confidence: 99%